สมรรถนะครูที่ส่งผลต่อการปฏิบัติงานด้านวิชาการในโรงเรียน สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาราชบุรี เขต 2 - คำยอด อรวรรณ; วังถนอมศักดิ์ มัทนา (วารสารการบริหารการศึกษา มหาวิทยาลัยศิลปากร, 2016)
การวิจัยครั้งนี้ มีวัตถุประสงค์เพื่อทราบ 1) สมรรถนะครูในโรงเรียน สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาราชบุรี เขต 2 2) การปฏิบัติงานด้านวิชาการในโรงเรียน สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาราชบุรี เขต 2 และ 3) สมรรถนะครูที่ส่งผลต่อการปฏิบัติงานด้านวิชาการในโรงเรียน สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาราชบุรี เขต 2 เครื่องมือที่ใช้เป็นแบบสอบถามเกี่ยวกับ สมรรถนะครูของพิมพ์พันธ์ เตชะคุปต์ และพรทิพย์ แข็งขัน และการปฏิบัติงานด้าน วิชาการของ สำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน กระทรวงศึกษาธิการ สถิติที่ใช้ในการวิเคราะห์ข้อมูล คือ ค่าความถี่ ค่าร้อยละ ค่ามัชฌิมเลขคณิต ส่วนเบี่ยงเบนมาตรฐาน และการวิเคราะห์การถดถอยพหุคูณแบบขั้นตอน ผลการวิจัยพบว่า 1. สมรรถนะครูในโรงเรียน สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาราชบุรี เขต 2 ทั้งในภาพรวมและรายด้านอยู่ในระดับมาก 2. การปฏิบัติงานด้านวิชาการในโรงเรียน สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาราชบุรี เขต 2 ทั้งในภาพรวมและรายด้านอยู่ในระดับมาก 3. สมรรถนะครูด้านสมรรถนะหลัก และสมรรถนะด้านประจำสายงานส่งผลต่อการปฏิบัติงานด้านวิชาการในโรงเรียนสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาราชบุรี เขต 2 อย่างมีนัยสำคัญทางสถิติ ที่ระดับ .01 TEACHER’S COMPETENCY AFFECTING ACADEMIC PERFORMANCE IN SCHOOL UNDER THE JURISDICTION OF RATCHABURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 The purposes of this study were to find 1) teacher’s competency in school under The Jurisdiction of Ratchaburi Primary Educational Service Area Office2, 2) academic performance in school under The Jurisdiction of Ratchaburi Primary Educational Service Area Office2, and 3) teacher’s competency affecting academic performance in school under The Jurisdiction of Ratchaburi Primary Educational Service Area Office2. The research instruments were questionnaire regarding the teacher’s competency based on the concept of Pimpan Tachakub and Porntip Kengkun and academic performance based on the concept of The Office of The Basic Education, The Ministry of Education. The statistics used to analyze the data were frequency, percentage, Arithmetic mean, standard deviation and stepwise multiple regression analysis. The results were found that 1. Teacher’s competency in school under The Jurisdiction of Ratchaburi Primary Educational Service Area Office2,overall and individually, was found at a high level. 2. Academic performance in school under The Jurisdiction of Ratchaburi Primary Educational Service Area Office2, overall and individually, was found at a high level. 3. Teacher’s competency : Core Competency and Functional Competency affected the academic performance in school under The Jurisdiction of Ratchaburi Primary Educational Service Area Office2 at .01 level of significance.